Advances in microbial corrosion of metals induced via extracellular electron transfer by Shewanella oneidensis MR-1 - Mohammed Arroussi; Ke Yang; Afaque Shams; Ihsan Ul Haq Toor; Boxin Wei (npj Materials Degradation)
Abstract S. oneidensis MR-1 is frequently used in microbial corrosion studies due to the electrochemical activity and the easy cultivation. However, corrosion mechanisms of S. oneidensis MR-1, as a dissimilatory metal-reducing bacterium (DMRB), sometimes appear contradictory. This paper comprehensively reviewed the corrosion mechanisms of S. oneidensis MR-1, and the components involved in extracellular electron transfer (EET). The review aims to reveal the complexity of the corrosion processes by S. oneidensis MR-1.